Effects of combining yeast products with antimicrobials in grain adaptation diets for feedlot Nellore bulls on performance, behavior, and metabolome - Ribeiro, Richard Vaquero; Baldassini, Welder Angelo; Cônsolo, Nara Regina Brandão; Moreira, José Breno da Silva; Torres, Rodrigo de Nazaré Santos; Galvão, Jean Lucas Carvalho; Chardulo, Luis Artur Loyola; Curi, Rogério Abdallah; Ribeiro, Gabriel Henrique; Colnago, Luiz Alberto; Machado Neto, Otávio Rodrigues (Frontiers in Animal Science, 2025)
This study evaluated the effects of different combinations of yeast products and antimicrobials during adaptation to high-grain feedlot diets on performance, feeding behavior, carcass traits, and the serum metabolome of feedlot Nellore bulls. One hundred twenty Nellore bulls were divided into two body weight groups and assigned within groups to 24 pens. The following dietary treatments were applied: MVY: monensin at 18 mg/kg of dry matter (DM) + virginiamycin at 15 mg/kg of DM + live yeast at 2 g/animal/day; NLY: narasin at 13 mg/kg of DM + live yeast at 2 g/animal/day; NYC: narasin at 13 mg/kg of DM + yeast culture at 7 g/animal/day; NDY: narasin at 13 mg/kg of DM + active dry yeast at 1 g/animal/day. Treatments were administered during the grain adaptation period (d1–d21). Blood samples were collected at the end of the grain adaptation period for serum metabolome profiling. During the 21-day grain adaptation period, bulls fed NYC tended (P = 0.09) to have a greater average daily gain than bulls fed MVY. Dry matter intake (DMI), final body weight, and feed efficiency were similar (P > 0.05) among treatments. During the finishing period, bulls fed NLY had a lower (P = 0.04) DMI as a percentage of body weight than bulls receiving MVY. There were no treatment effects (P > 0.05) on the carcass traits. Bulls fed NDY spent more time resting (P = 0.03) and tended (P ≤ 0.10) to have fewer meals per day and greater DMI per meal than animals fed MVY. Lactate was the most important serum metabolite for discriminating all treatment groups, with a higher concentration in the MVY group. The three most important metabolites for discriminating the MVY and NLY groups were lactate, creatine, and valine, whose concentrations were higher in the MVY group. The three most important metabolites for discriminating MVY and NYC were 3-phenylpropionate, hippurate, and betaine, whose concentrations were higher in the NYC group. Thus, narasin can replace the combination of monensin and virginiamycin in high-grain adaptation diets for Nellore bulls when administered together with yeast products, with the NYC combination showing great potential.